On generalized Bell polynomials - Corcino, Roberto B. (Animo Repository, 2011)
It is shown that the sequence of the generalized Bell polynomials S n(x) is convex under some restrictions of the parameters involved. A kind of recurrence relation for S n(x) is established, and some numbers related to the generalized Bell numbers and their properties are investigated. Copyright © 2011 Roberto B. Corcino and Cristina B. Corcino.